Determinants of knowledge sharing behavior in the timber industry of Sibu, Sarawak - Hii, Yu Hieng (Universiti Malaysia Sarawak (UNIMAS), 2012)
Timber industry has becomes one of the key contributor to the growth of Sarawak's gross domestic products and socio-economic development. It is believed that its long term competitiveness in the global markets and sustainable development can be achieved through extensive and effective knowledge sharing among the organization employees. Thus, a research model based on Ajzen's (1991) theory of planned behavior (TPB) was developed in this study to examine the direct impact of potential influential determinants on the knowledge sharing behavior of middle-level management employees in the timber organizations of Sibu, Sarawak.